40 days and 40 nights: Clinical characteristics of major trauma and orthopaedic injury comparing the incubation and lockdown phases of COVID-19 infection. (2020) - Ajayi, Bisola; Trompeter, Alex; Arnander, Magnus; Sedgwick, Philip; Lui, Darren F.
Abstract : Aims: The first death in the UK caused by COVID-19 occurred on 5 March 2020. We aim to describe the clinical characteristics and outcomes of major trauma and orthopaedic patients admitted in the early COVID-19 era. Methods: A prospective trauma registry was reviewed at a Level 1 Major Trauma Centre. We divided patients into Group A, 40 days prior to 5 March 2020, and into Group B, 40 days after. Results: A total of 657 consecutive trauma and orthopaedic patients were identified with a mean age of 55 years (8 to 98; standard deviation (SD) 22.52) and 393 (59.8%) were males. In all, 344 (approximately 50%) of admissions were major trauma. Group A had 421 patients, decreasing to 236 patients in Group B (36%). Mechanism of injury (MOI) was commonly a fall in 351 (52.4%) patients, but road traffic accidents (RTAs) increased from 56 (13.3%) in group A to 51 (21.6%) in group B (p = 0.030). ICU admissions decreased from 26 (6.2%) in group A to 5 (2.1%) in group B. Overall, 39 patients tested positive for COVID-19 with mean age of 73 years (28 to 98; SD 17.99) and 22 (56.4%) males. Common symptoms were dyspnoea, dry cough, and pyrexia. Of these patients, 27 (69.2%) were nosocomial infections and two (5.1%) of these patients required intensive care unit (ICU) admission with 8/39 mortality (20.5%). Of the patients who died, 50% were older and had underlying comorbidities (hypertension and cardiovascular disease, dementia, arthritis). Conclusion: Trauma admissions decreased in the lockdown phase with an increased incidence of RTAs. Nosocomial infection was common in 27 (69.2%) of those with COVID-19. Symptoms and comorbidities were consistent with previous reports with noted inclusion of dementia and arthritis. The mortality rate of trauma and COVID-19 was 20.5%, mainly in octogenarians, and COVID-19 surgical mortality was 15.4%. Cite this article: Bone Joint Open 2020;1-7:330–338.